Benzothiazole Treatment Regulates the Reactive Oxygen Species Metabolism and Phenylpropanoid Pathway of Rosa roxburghii Fruit to Delay Senescence During Low Temperature Storage - Dong, Boyu; Tang, Hongmin; Zhu, Dequan; Yao, Qiuping; Han, Hongqiang; He, Kequn; Ding, Xiaochun (Frontiers in Plant Science, 2021)
Rosa roxburghii fruits were used as research objects to study the effects of different concentrations of benzothiazole (BTH) treatment on quality parameters, reactive oxygen species (ROS) metabolism, and the phenylpropanoid pathway at a low temperature (4 °C; relative humidity: 40%–45%). Results showed that BTH effectively delayed senescence and maintained the quality of R. roxburghii fruits. BTH effectively suppressed weight loss and malondialdehyde content; it also enhanced total soluble solid content, titratable acidity, and cell membrane integrity. Moreover, BTH increased hydrogen peroxide content, superoxide anion production rate, and the activities and expression of superoxide dismutase, catalase, ascorbate peroxidase, glutathione reductase, monodehydroascorbate reductase, dehydroascorbate reductase, peroxidase, glutathione, and ascorbic acid. In addition, the activities and gene expression of phenylalanine ammonia lyase, cinnamate 4-hydroxylase, and 4-coumarate-CoA ligase and the concentrations of flavonoids, total phenols, and lignin were significantly elevated by BTH. The findings imply that BTH can delay senescence in and maintain the quality of R. roxburghii fruits by modulating ROS metabolism and the phenylpropanoid pathway under low-temperature conditions.